Free convection heat transfer and flow field in triangular enclosures filled with porous media - Varol, Yasin; Öztop, Hakan Fehmi R.; Varol, Asaf (Begell House Inc, 2008)
Steady state two-dimensional natural convection heat transfer was performed in triangular enclosures filled with porous media at different boundary conditions. Six different cases were tested based on all possibilities of temperature boundary conditions on vertical, bottom, and inclined walls of enclosure. Solutions of governing equations and linear algebraic equations were performed by the central difference and the successive underrelaxation method, respectively. Flow patterns and temperature distributions were presented at different aspect ratios (0.25 <= AR <= 2) and Rayleigh numbers (100 <= Ra <= 1000). On the basis of the results, it is observed that when a heater was located at the bottom wall, multiple vortexes were formed, and the highest heat transfer is obtained according to the mode of other cases.
Keywords: Natural-Convection; Cavity; Wall